2010
DOI: 10.1364/oe.18.023784
|View full text |Cite
|
Sign up to set email alerts
|

GHz-bandwidth optical filters based on high-order silicon ring resonators

Abstract: Previously demonstrated high-order silicon ring filters typically have bandwidths larger than 100 GHz. Here we demonstrate 1-2 GHz-bandwidth filters with very high extinction ratios (~50 dB). The silicon waveguides employed to construct these filters have propagation losses of ~0.5 dB/cm. Each ring of a filter is thermally controlled by metal heaters situated on the top of the ring. With a power dissipation of ~72 mW, the ring resonance can be tuned by one free spectral range, resulting in wavelength-tunable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(78 citation statements)
references
References 11 publications
1
77
0
Order By: Relevance
“…While this is difficult to achieve with all-electronic filters [3][4][5][6][7], integrated microwave photonic (IMWP) filters [8] can readily achieve multi-gigahertz tuning range without significant degradation in their frequency response. However, these filters typically exhibit limited resolution (GHz instead of MHz linewidths) and are plagued by trade-offs between key parameters, such as between the frequency tuning range and the resolution for multi-tap filters [9][10][11][12][13]; or between the peak rejection and the resolution for resonator-based filters [14][15][16][17][18].Stimulated Brillouin scattering (SBS) [19][20][21][22] offers a route to MHz-resolution IMWP filters. Although SBS has been widely studied in optical fibers, recently there has been a growing interest in harnessing SBS in nanophotonic waveguides [22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…While this is difficult to achieve with all-electronic filters [3][4][5][6][7], integrated microwave photonic (IMWP) filters [8] can readily achieve multi-gigahertz tuning range without significant degradation in their frequency response. However, these filters typically exhibit limited resolution (GHz instead of MHz linewidths) and are plagued by trade-offs between key parameters, such as between the frequency tuning range and the resolution for multi-tap filters [9][10][11][12][13]; or between the peak rejection and the resolution for resonator-based filters [14][15][16][17][18].Stimulated Brillouin scattering (SBS) [19][20][21][22] offers a route to MHz-resolution IMWP filters. Although SBS has been widely studied in optical fibers, recently there has been a growing interest in harnessing SBS in nanophotonic waveguides [22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…Preliminary efforts towards integration have relied on resonant delay lines provided by ring cavities and coupled resonant optical waveguides [17][18][19][20] . These approaches suffer from an intrinsic trade-off between dispersion and bandwidth, preventing broadband operation.…”
mentioning
confidence: 99%
“…The processor chips feature a waveguide propagation loss of 0.25 dB/cm and a filter bandwidth smaller than 1 GHz for an FSR of 13.5 GHz. In Dong et al [99], demonstrated silicon processor chips comprising coupled RRs up to fifth order as shown in Figure 22, which feature a propagation loss of 0.5 dB/m and provide bandpass filters with GHz-level bandwidths. Also in silicon waveguides, Orlandi et al…”
Section: Various Filter Implementationsmentioning
confidence: 99%